Evaluating TPACK of Geography Teachers to Support Continuous Professional Development in Yogyakarta Private High Schools - Jihan Fadhila; Muhammad Nursa'ban (JPG (Jurnal Pendidikan Geografi), 2026)
Professional teachers must have adequate TPACK (Technological Pedagogic Content Knowledge) competencies. Research objectives: (1) To assess the level of understanding and application of TPACK by geography teachers based on certification status and school accreditation (2) To reveal the support and obstacles faced by geography teachers in implementing TPACK. This study applied a quantitative descriptive approach using the CIPP (Context, Input, Process, Product) evaluation model. The sample in this study consisted of 40 geography teachers. Based on the quantitative data analysis it was found that the average TPACK score of certified teachers reached 73.25, reflecting a relatively high level of understanding and application. Meanwhile, non-certified teachers have an average score of 53.7 which is in the moderate to low category. In the context aspect showed a significant difference between certified and non-certified teachers, with certified teachers having higher and more stable TPACK scores than non-certified teachers. In the input, it was found that the level of school accreditation influenced the readiness of supporting resources for TPACK implementation. The process evaluation revealed that despite various forms of support, such as facilities, training, and teacher collaboration, the TPACK implementation process still faced obstacles such as infrastructure limitations, low ICT competence, workload, and student readiness. In the product, this study recommends strengthening the continuing professional development program through contextual training, strengthening the teacher community, implementing mentoring, increasing school support, and continuous evaluation. Kata kunci: TPACK, CIPP, Guru Geografi